Analisis Faktor Keterlambatan Menggunakan Metode CPM pada Proyek Konstruksi Bangunan Gedung RKB MIN 5 Maluku Tengah - Kapitanhitu, Maryam; Saleh, La Mohamat; Abdin, Maslan (JURNAL ILMIAH NUSANTARA, 2025)
A construction project is a series of interrelated activities to of interrelated activities to achieve goals within certain time, cost, and quality constraints. Constraints can also of a building. The construction of a classroom construction project with the aim of producing a physical building that meets the requirements of quality, cost, and time. Project delays caused by service providers, service users, and other parties involved in project activities can result in additional contract time and costs. Where delays in the project always result in losses experienced by all parties involved in the project. In this case, it is about what causes delays, demands for completion time and completion costs. Therefore, this research will analyze the delay factors using the CPM method on the RKB min 5 malteng building construction project which includes the levels of delay in the project.